2022
DOI: 10.1038/s41467-022-35323-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of heart failure with preserved versus reduced ejection fraction

Abstract: Pharmacologic clinical trials for heart failure with preserved ejection fraction have been largely unsuccessful as compared to those for heart failure with reduced ejection fraction. Whether differences in the genetic underpinnings of these major heart failure subtypes may provide insights into the disparate outcomes of clinical trials remains unknown. We utilize a large, uniformly phenotyped, single cohort of heart failure sub-classified into heart failure with reduced and with preserved ejection fractions ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 85 publications
0
30
0
Order By: Relevance
“…In addition, recent large studies suggest a lack of association between human genetic variation and subtypes of HF (HFpEF vs. HFrEF), suggesting that more phenotype-adjacent marks of HF status may provide more resolution. 5 The circulating transcriptome has therefore been an area of active mechanistic investigation in human HF. Previous studies utilizing cell-based transcriptomics (e.g., peripheral immune profile) or “cell-free” transcriptomics (e.g., circulating miRNAs, lncRNAs) have been successful (specifically with lncRNAs 29 ), though with variable results likely due to several factors such as single time-point study, low-input quantity, RNA fragmentation, and differences in quantification platform and population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent large studies suggest a lack of association between human genetic variation and subtypes of HF (HFpEF vs. HFrEF), suggesting that more phenotype-adjacent marks of HF status may provide more resolution. 5 The circulating transcriptome has therefore been an area of active mechanistic investigation in human HF. Previous studies utilizing cell-based transcriptomics (e.g., peripheral immune profile) or “cell-free” transcriptomics (e.g., circulating miRNAs, lncRNAs) have been successful (specifically with lncRNAs 29 ), though with variable results likely due to several factors such as single time-point study, low-input quantity, RNA fragmentation, and differences in quantification platform and population.…”
Section: Discussionmentioning
confidence: 99%
“…The median (IQR) time between admission and initial blood draw was 2 (1-3) days for the discovery cohort and 3 (2-4) days for the validation cohort. The median (IQR) hospital stay was 6 (3)(4)(5)(6)(7)(8) days in the discovery cohort and 5 (3-7) days in the validation cohort. The median (IQR) time between the final blood draw and discharge was 1 (1-3) day in both cohorts.…”
Section: Cohort Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, HF can be classified into three subtypes based on LVEF level, including HF with reduced ejection fraction (HFrEF), HF with mid-range ejection fraction (HFmrEF), and HF with preserved ejection fraction (HFpEF) according to the ESC guidelines, and previous observational studies identified divergent risk factor profiles for these HF subtypes (Dunlay et al, 2017;McDonagh et al, 2021). Moreover, recent genetic studies found pronounced differences in the genetic architectures of HFrEF and HFpEF (Bielecka-Dabrowa et al, 2016;Joseph et al, 2022). For example, a recent large GWAS by Joseph et al found 13 loci associated with HFrEF, but only one associated with HFpEF at genome-wide significance despite a robust sample size, indicating that HFpEF is likely to be a collective syndrome representing several different pathophysiological entities (Joseph et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Moreover, recent genetic studies found pronounced differences in the genetic architectures of HFrEF and HFpEF (Bielecka-Dabrowa et al, 2016;Joseph et al, 2022). For example, a recent large GWAS by Joseph et al found 13 loci associated with HFrEF, but only one associated with HFpEF at genome-wide significance despite a robust sample size, indicating that HFpEF is likely to be a collective syndrome representing several different pathophysiological entities (Joseph et al, 2022). Therefore, the causal factors identified from MR analysis by combing all kinds of HF as an outcome may not play etiological roles in HFpEF.…”
Section: Figurementioning
confidence: 99%